The Impact of Socioeconomic Status on Visual Acuity Changes in Schoolchildren: A One-Year Follow-Up - Alba Galdón; Núria Vila-Vidal; Mariam El Gharbi; Valldeflors Vinuela-Navarro; Joan Pérez-Corral; Núria Tomás; Laura Guisasola (MDPI AG, 2024)
(1) Background: Visual acuity (VA) is essential for children's quality of life, and its relationship with socioeconomic status (SES) highlights disparities in healthcare. This study investigated the influence of SES on changes in schoolchildren's VA over one year. (2) Methods: Initial examinations were conducted on 1822 children (8-10 years). Follow-up was performed on 804 of these children a year later. Uncorrected (UCVA) and presenting (PVA) distance VA were measured monocularly using a decimal Snellen chart. Very reduced UCVA (<0.5) was considered a proxy of myopia. (3) Results: The prevalence of initially very reduced UCVA (myopia) was similar in children with low and high SES (12.6% vs. 12.4%) (χ2; p = 0.153). After one year, the prevalence of very reduced UCVA increased to 14.1% in children with a low SES compared with 11.1% in children with a high SES (p = 0.001). Significant disparities related to SES were also found in PVA so that children with a low SES exhibited a greater reduction in PVA than children with a high SES (5.2% vs. 3.5%) (χ2; p = 0.004). (4) Conclusions: Children with a low SES showed an increase in reduced UCVA values over one year and a higher number of children with very reduced PVA compared with those with a high SES.